The MyFlex-ζ Foot: A Variable Stiffness ESR Ankle-Foot Prosthesis - Johnnidel Tabucol; Vera G. M. Kooiman; Marco Leopaldi; Ruud Leijendekkers; Giacomo Selleri; Marcello Mellini; Nico Verdonschot; Magnus Oddsson; Raffaella Carloni; Andrea Zucchelli; Tommaso M. Brugo (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Most commercially available foot prostheses are passive ESR feet, which store and release energy to reduce metabolic costs and improve comfort but cannot adjust to varying walking conditions. In contrast, bionic feet adapt to different tasks but are hindered by high weight, power consumption, and cost. This paper presents MyFlex- $ζ $ , an ESR foot with a variable stiffness system, as a compromise between these two categories. MyFlex- $ζ $ adjusts stiffness by varying the sagittal-plane distance between two key points, altering force interactions within the prosthesis and affecting overall stiffness. Clinical tests with three transfemoral amputees evaluated stiffness variation across two sessions: the first subjective, where participants assessed stiffness settings during different tasks, and the second biomechanical, measuring performance parameters. Two participants selected different stiffness settings for various tasks, while the third, with limited perception of stiffness changes, showed less distinction in outcomes. Greater sagittal-plane rotation and higher energy absorption were observed in most tasks with more compliant settings, although one participant’s results were limited due to selecting close stiffness settings. Overall, these findings suggest MyFlex- $ζ $ offers adaptability and performance improvements over traditional ESR feet. With further actuation and control system development, MyFlex- $ζ $ could mark significant progress in prosthesis technology.